GP98 IL1- β levels at presentation with paediatric mild traumatic brain injury are higher in children with previous mild traumatic head injuries. (June 2019) - Ryan, Emer; Kelly, Lynne; Bolger, Turlough; Molloy, Eleanor
Abstract : Aims: To evaluate end components of the innate immune system, the inflammsome, in mild Traumatic Brain Injury (TBI), a pathway activated in mild tramatic brain injury and to correlate with previous exposure to head injury. Methods: Whole blood was sampled from children with mild TBI at presentation with injury and compared to healthy paediatric controls at baseline. RNA was isolated and cDNA was synthesized. Gene Expression of IL-1 β via rtPCR was recorded in 18 patients 5 controls at baseline. Of 18 patients, 10 had previously suffered concussion. Results: Mechanisms of injury included sporting and school yard clashes, falls from bikes and falls from bed. GCS was 14 – 15/15 in all. Inflammasome was upregulated via IL-1 β expression in children with previous episodes of mTBI compared to those with no previous history. (p = 0.08) The highest IL-1 β, 8000 fold that of baseline. This was recorded in a child who had previously had rehabilitation following a road traffic accident 7 years previously. Conclusion: Inflammation is altered in TBI compared to controls. IL-1 β gene transcription was higher in those with previous episodes of concussion. Immune memory may be a factor in the clinically evident burden of symptoms following repetitive head trauma, and this warrants further exploration.